A Study on the Socio-economic impact of Leasing Activities in Jaffna District - Rajan, T. (My University, 2022)
The financial leasing activities significantly increased in the Jaffna District after 2009. The people in this district have got access to the leasing services in order to fulfill their various needs, but the default rate of leasing has increased for many reasons. As leasing companies repossessed leased assets, customers lost their investment and faced many socio-economic problems. The study aims to investigate the socio-economic impacts of leasing activities in Jaffna District. For this study, 331 lessees were randomly selected to collect data. Descriptive and regression analysis was conducted. This study has found that 85% of lessees invested in vehicles. Around 40% of the lessees are self-employed and invested in business ventures. The average leasing rate is around 28%. The findings of regression analysis show that the lessee who is self-employed and invested in his/her own business earns a higher monthly income than others. Increase in leasing amount alone will not create significant employment. The lessee who is self-employed and invested in his/her own transport business creates employment two times greater when compared with others. Leasing has significantly increased monthly household expenditure, household equipment and improved housing conditions, while 40% of lessees defaulted. Initial income, assets of lessee, leasing amount and increase in income decrease the default rate, but the amount of debt and increase in household expenditure increase the default rate. The impact of household expenditure on the default rate is approximately six times greater than the impact of income on the default rate. The study found household expenditure as the main factor which increased the default rate. This study concludes that, on average, the leasing has contributed to a moderate positive socio- economic impact in the Jaffna District. The qualitative analysis shows that the leasing activity has created many social issues. Therefore, this study would recommend that leasing companies should carefully study the initial income, assets, debts of the lessee, and their willingness to invest in their own business. The leasing companies should provide free advice and information service to the lessee in managing business and household expenditures. The government authorities should monitor leasing activities and have control over leasing rates to avoid over-exploitation of the lessees.
Keywords: Default rate; Leasing facility; Leasing rate; Regression analysis; Socio-economic impact